4x-7-36=0

Simple and best practice solution for 4x-7-36=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-7-36=0 equation:


Simplifying
4x + -7 + -36 = 0

Reorder the terms:
-7 + -36 + 4x = 0

Combine like terms: -7 + -36 = -43
-43 + 4x = 0

Solving
-43 + 4x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '43' to each side of the equation.
-43 + 43 + 4x = 0 + 43

Combine like terms: -43 + 43 = 0
0 + 4x = 0 + 43
4x = 0 + 43

Combine like terms: 0 + 43 = 43
4x = 43

Divide each side by '4'.
x = 10.75

Simplifying
x = 10.75

See similar equations:

| 3m+(5+m)+5= | | 7(5+3r)=203 | | 4y-9=10 | | 4.25/0.75 | | 4x-7+6x=13-10 | | (x+4)(x+5)=1 | | x+10-15=0 | | 14+5x+2x=49 | | 2.840=1.2x-0.2x^2 | | -8y-7=9 | | 3(y+2)=2y+13 | | 7n+8n=-33 | | -8-2x+13=11+5x+57 | | 2x+17=-(3-7x) | | 4-4*5+4= | | 1.64=0.5x-0.2x^2 | | 9x^3+6x^2-9x=0 | | 12-1.5x/3 | | 3y+2=2y+13 | | -1/5b-2/5=-5 | | 250/298=x/368 | | -12a+8=-28 | | N+-4=-11 | | (32b)^(2/3) | | 3•5/13 | | (3x+5)(5x-2)=0 | | 4+2(7r-4)=-116 | | 2=0.15x^2+1 | | (((2z)^(1/5))^4)/(z^(1/20)) | | 4+2(7r-r)=-116 | | 5=0.55x^2+1 | | (((2z)^(1/5))^4)/z^(1/20) |

Equations solver categories